Encontros formativos: um estudo sobre a avaliação externa e a escala de proficiência na escola de ensino integral - Longo, Cássia Moraes Targa (2019)
This master’s has overall objective to analyze, what managers and teachers understanding by large-scale proficiency evaluation, how the results of these evaluations are used in formative meetings. The point is : what factors have contributed to the poor performance of students in external assessment (Saresp), in the final years of elementary school, in the subjects of Portuguese Language and Mathematics? The theoretical framework adopted was os constructos de Freitas (2002), Vianna (2002), Ristoff (1996), Santos (2015), André (2014), and others. The methodology is qualitative, with formative meetings, exploring different techniques of data production, such as: individual written records of participants, reflective group records and researcher records, as well as official Saresp documents. The participants are managers and teachers who work in the final years of elementary school and high school, in a special program of São Paulo’s government called Integral Education Program. The formative meetings made it possible to identify obstacles and possibilities for pedagogical management in the themes and concepts that involve external evaluation, the proficiency scale and the skills and competences. In this case, the group expressed a critical reflection on the policy of evaluative culture in the school, through investigative posture. However, the results also indicate that managers and teachers have divergent understandings about external assessment and proficiency scale. Thus, the uses of the results of these evaluations should be studied and interpreted in collective meetings, so that they can be understood as support for assertive decision making. The continuous learning in assessment need to be continuity within the school, from a critical-reflexive perspective, and this final work contributes to the interpretation of educational outcomes with a view to improving the quality of teaching